2013
DOI: 10.1007/s13277-013-1351-5
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of RECQL5 gene and laryngeal cancer

Abstract: RECQL is a DNA helicase involved in DNA mismatch repair. Previous studies indicated that the RECQL gene mutation was associated with human cancers. In the present study, we investigated the association between polymorphisms of RECQL gene and laryngeal cancer in a Chinese population. Four polymorphisms of the RECQL5 gene (rs820186, rs820196, rs820200, and rs4789223) were genotyped by the TaqMan method in 275 patients with larynx cancer and 300 age- and sex-matched non-cancer controls. We found that rs820196 pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Recent publications indicated that the genetic polymorphisms of RECQL5 are associated with human cancer, such as laryngeal cancer [17] and osteosarcoma [16]. Zhi et al [16] explored the relation between osteosarcoma risk and RECQL5 polymorphism and found that the CC genotype in rs820196 (17.5 vs 8.3 %, P=0.005) and AA genotype in rs4789223 (21.7 vs 14.2 %, P<0.001) were more frequent in the osteosarcoma group compared to the control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent publications indicated that the genetic polymorphisms of RECQL5 are associated with human cancer, such as laryngeal cancer [17] and osteosarcoma [16]. Zhi et al [16] explored the relation between osteosarcoma risk and RECQL5 polymorphism and found that the CC genotype in rs820196 (17.5 vs 8.3 %, P=0.005) and AA genotype in rs4789223 (21.7 vs 14.2 %, P<0.001) were more frequent in the osteosarcoma group compared to the control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Zhi et al [16] explored the relation between osteosarcoma risk and RECQL5 polymorphism and found that the CC genotype in rs820196 (17.5 vs 8.3 %, P=0.005) and AA genotype in rs4789223 (21.7 vs 14.2 %, P<0.001) were more frequent in the osteosarcoma group compared to the control group, respectively. Qi et al [17] studied the association between laryngeal cancer risk and RECQL5 polymorphisms and found that the rs820196 polymorphism of RECQL5 was associated with larynx cancer; the CC genotype (16.4 vs 9.3 %, P=0.013) and C allele (42 vs 34.2 %, P=0.006) were common in larynx cancer patients than in the control subjects, respectively. However, rs4789223 was not found to be associated with larynx cancer in Qi et al's study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations